Export potential of the agricultural sector of Ukraine under the global regulation of international trade (Revista de Ciências Agroveterinárias, 2024)
The relevance of the study lies in its. emphasis on identifying the key factors that enhance the export potential of Ukraine's agricultural sector, with a focus on the regulatory frameworks governing international grain trade. The purpose is to develop a mechanism ensuring the global competitive positioning of Ukraine's agricultural sector by utilizing specialized export-logistics services. The main findings include the creation of a comprehensive methodological toolkit for  evaluating export potential, its key determinants, and Ukraine's grain production share in EU trade. The study also forecasts foreign exchange earnings and predicts a decline in wheat and corn exports due to the ongoing war. The study emphasizes that maximizing export potential is a strategically planned and tactically verified process, requiring the development of robust personnel, resource, infrastructure, and logistics systems to strengthen Ukraine's position in the international market. The study concludes on the necessity for a carefully strategized export policy to mitigate negative globalization impacts and foster international cooperation, ultimately transitioning Ukraine from a raw material exporter to a supplier of high-quality, value-added products.
Keywords: export potential; agrarian sector of the economy; branch of agriculture; export quota; subjects of grain production